Microbial occupational exposure assessments in sawmills: a review - Dias, Marta (2022)
The composition of airborne microflora in sawmills may vary to a great degree depending on the kind of timber being processed and the technology of production being used. Cases of allergy alveolitis and asthma have been reported in woodworkers who were exposed to wood dust largely infected with microorganisms. The aim of this review article is to identify studies where the microbial occupational exposure assessment was performed in sawmills and the characteristics of the contamination found, as well as to identify which sampling methods and assays were applied. This study reports the search of available data published regarding microbial occupational exposure assessment in environmental samples from sawmills, following the Preferred Reporting Items for Systematic Reviews (PRISMA) methodology. The most used sampling method was air sampling, impaction being the most common method. Regarding analytical procedures for microbial characterization, morphological identification of fungi and bacteria was the most frequent approach. Screening for fungal susceptibility to azoles was performed in two studies and four studies applied molecular tools. Regarding microbial contamination, high fungal levels were frequent, as well as high bacteria levels. Fungal identification evidenced Penicillium as the most frequent genera followed by Aspergillus sp. Mycotoxins were not assessed in any of the analyzed studies. Microbial occupational exposure assessment in sawmills is crucial to allow this risk characterization and management.